Analytical framework for ex‐post evaluation of transport projects: Lessons learnt on retrospective CBA. Issue 3 (7th January 2020) - Vignetti, Silvia; Giffoni, Francesco; Pancotti, Chiara; Pagliara, Francesca
Abstract: This study deals with the ex‐post evaluation of ten major transport projects which were co‐financed by the European Regional Development Fund and the Cohesion Fund in the period 2000–2013 and located across nine EU Member States. The original contribution of this study is represented by the combination of the traditional ex‐post Cost–Benefit approach with a qualitative analysis. Specifically, a retrospective Cost–Benefit analysis is used to quantify the benefits and costs of the projects, then interviews to relevant stakeholders were carried out. Ex‐post CBA, when appropriately implemented and integrated with qualitative evidence, represents a powerful tool for supporting decision‐making processes and for policy lessons. Resumen: El presente estudio se ocupa de la evaluación a posteriori de diez proyectos de transporte importantes que fueron cofinanciados por el Fondo Europeo de Desarrollo Regional y el Fondo de Cohesión en el período 2000‐2013, distribuidos en nueve Estados miembros de la UE. La contribución original de este estudio está representada por la combinación del enfoque tradicional de costo‐beneficio a posteriori con un análisis cualitativo. En concreto, se utilizó un análisis a posteriori de costo‐beneficio para cuantificar los beneficios y los costos de los proyectos, tras lo cual se realizaron entrevistas a los interesados pertinentes. El análisis a posteriori de costo‐beneficio, cuando se aplica adecuadamente y se combina con pruebas cualitativas, representa un poderoso instrumento de apoyo a los procesos de toma de decisiones y de aprendizaje en materia de políticas. 抄録: 本稿では、2000~2013年に欧州地域開発基金(European Regional Development Fund)と結束基金 (Cohesion Fund)の共同出資を受けた、EUの9つの加盟国における10件の主要交通プロジェクトの事後評価を行う。本研究の独自の寄与は、定量分析を含む因習的な費用便益の事後評価法により提示される。具体的には、プロジェクトの利益とコストを定量するために遡及的な費用便益分析を行い、その次に重要な利害関係者への聴取調査を行う。費用便益の事後評価は、適切に実施され質的エビデンスと統合されれば、意思決定のプロセスの支援および政策に関する教訓のための強力なツールとなる。